Ambassadors of knowledge sharing: Co-produced travel information through tourist-local social media exchange. Issue 2 (13th February 2017) - Edwards, Deborah; Cheng, Mingming; Wong, IpKin Anthony; Zhang, Jian; Wu, Qiang
Abstract : Purpose: The aim of this study is to understand the knowledge-sharing structure and co-production of trip-related knowledge through online travel forums. Design/methodology/approach: The travel forum threads were collected from TripAdvisor's Sydney travel forum for the period from 2010 to 2014, which contains 115, 847 threads from 8, 346 conversations. The data analytical technique was based on a novel methodological approach – visual analytics, including semantic pattern generation and network analysis. Findings: Findings indicate that the knowledge structure is created by community residents who camouflage as local experts and serve as ambassadors of a destination. The knowledge structure presents collective intelligence co-produced by community residents and tourists. Further findings reveal how these community residents associate with each other and form a knowledge repertoire with information covering various travel domain areas. Practical implications: The study offers valuable insights to help destination-management organizations and tour operators identify existing and emerging tourism issues to achieve a competitive destination advantage. Originality/value: This study highlights the process of social media mediated travel knowledge co-production. It also discovers how community residents engage in reaching out to tourists by camouflaging as ordinary users.